PENGEMBANGAN APLIKASI BERBASIS ANDROID ALE “ASEAN LEARN“ UNTUK SISWA SEKOLAH DASAR KELAS VI - Azhary, Putri Aulia; Hanifah, Nurdinah; Aeni, Ani Nur (JUTECH : Journal Education and Technology, 2024)
This research is based on the lack of utilisation of technology in learning so that less optimal learning is done. This study aims to develop an android-based learning application using the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted in class VI at a public elementary school in West Jakarta with a total of 30 respondents with individual, small group, and large group trials. The results of the validity test conducted to media experts and material experts, both get a percentage of 92% which proves that this application is very feasible. The results of the individual, small group, and large group tests resulted in an average value of 85% which can indicate a very feasible predicate. The acquisition of student learning outcomes with the N-gain test obtained 0.6329 in 63% percent which is included in the moderate category and it can be concluded that there is an increase in learning outcomes after the use of the ALE application.